2006
DOI: 10.1128/jb.00766-06
|View full text |Cite
|
Sign up to set email alerts
|

Two Genes Encoding New Carotenoid-Modifying Enzymes in the Green Sulfur Bacterium Chlorobium tepidum

Abstract: The green sulfur bacterium Chlorobium tepidum produces chlorobactene as its primary carotenoid. Small amounts of chlorobactene are hydroxylated by the enzyme CrtC and then glucosylated and acylated to produce chlorobactene glucoside laurate. The genes encoding the enzymes responsible for these modifications of chlorobactene, CT1987, and CT0967, have been identified by comparative genomics, and these genes were insertionally inactivated in C. tepidum to verify their predicted function. The gene encoding chlorob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…Because horizontal transfer of carotenoid biosynthetic genes appears to occur frequently between unrelated microorganisms (54,55), this distribution leads one to question why cruA, as well as crtP, crtQ, and crtH, have not been transferred more broadly. The genes encoding phytoene synthases, CrtI-type carotenoid desaturases, and carotenoid glycosyltransferases are found not only in photosynthetic bacteria but also in Deinococcus radiodurans, the planctomycete Rhodopirellula baltica, actinomycetes, and archaea (17,24,25,51). The restricted distribution of CruA might indicate that some CruA cyclases require another protein subunit or a cofactor that is not commonly synthesized by many bacteria for optimal activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because horizontal transfer of carotenoid biosynthetic genes appears to occur frequently between unrelated microorganisms (54,55), this distribution leads one to question why cruA, as well as crtP, crtQ, and crtH, have not been transferred more broadly. The genes encoding phytoene synthases, CrtI-type carotenoid desaturases, and carotenoid glycosyltransferases are found not only in photosynthetic bacteria but also in Deinococcus radiodurans, the planctomycete Rhodopirellula baltica, actinomycetes, and archaea (17,24,25,51). The restricted distribution of CruA might indicate that some CruA cyclases require another protein subunit or a cofactor that is not commonly synthesized by many bacteria for optimal activity.…”
Section: Discussionmentioning
confidence: 99%
“…12, 13, and 51). The other genes in the chlorobactene biosynthetic pathway were identified on the basis of their similarity to genes involved in carotenoid biosynthesis in other organisms, and their functions were confirmed by targeted gene inactivation (12,51). However, this approach failed to identify the lycopene cyclase in C. tepidum (12), and, consequently, a complementation assay was used to identify the gene encoding the lycopene cyclase in GSB.…”
Section: Discussionmentioning
confidence: 99%
“…Homologs to other carotenoid biosynthetic genes in the genomes of GSB were also identified by using the predicted amino acid sequences of carotenoid biosynthesis genes from C. tepidum as queries in tblastn searches (21,36). A gene was considered orthologous if the E value of the match between the C. tepidum query sequence and its best match in another genome was less than 10 Ϫ80 .…”
Section: Methodsmentioning
confidence: 99%
“…We also performed a BLAST search analysis with a cyanobacterial MGlcDG synthase and found that an ORF, CT1987, showed the highest identity (;20%) to the enzyme. However, CT1987 is a chlorobactene glucosyltransferase (named CruC) involved in carotenoid modification in this bacterium (Maresca and Bryant, 2006). These observations suggested that C. tepidum does not have any orthologs for either planttype MGDG synthases or cyanobacterial MGlcDG synthases.…”
Section: Galactolipid Roles In Photosynthesis 2645mentioning
confidence: 82%